2016
DOI: 10.1080/09513590.2016.1197196
|View full text |Cite
|
Sign up to set email alerts
|

Luteal phase clomiphene citrate for ovulation induction in women with polycystic ovary syndrome: a systematic review and meta-analysis

Abstract: It appeared that late luteal phase CC for ovulation induction might be an effective method for ovulation induction in women with PCOS compared to conventional CC administration. Further intensive randomized-controlled studies should be warranted to define the efficacy of CC used in late luteal phase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Most of the systematic reviews comparing ovulation induction drugs in women with WHO group II ovulatory disorders have not reported on EMT. Ding et al . compared CC used in the luteal phase vs CC used in the follicular phase and found significantly thicker EMT in the latter group after pooled analysis of four studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the systematic reviews comparing ovulation induction drugs in women with WHO group II ovulatory disorders have not reported on EMT. Ding et al . compared CC used in the luteal phase vs CC used in the follicular phase and found significantly thicker EMT in the latter group after pooled analysis of four studies.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the systematic reviews comparing ovulation induction drugs in women with WHO group II ovulatory disorders have not reported on EMT 4,7,56-62 . Ding et al 63 compared CC used in the luteal phase vs CC used in the follicular phase and found significantly thicker EMT in the latter group after pooled analysis of four studies. Another meta-analysis reported mid-cycle EMT in five studies but pooled analysis was not performed due to the significant heterogeneity 64 .…”
Section: Comparison With Previous Reviewsmentioning
confidence: 99%
“…Luteal ovulation induction is a concept which was first introduced in ART for fertility preservation purposes in oncological cases [86]. It has recently been introduced as a way to increase success rates in women with PCOS or in women with poor ovarian reserve either alone or in combination with follicular phase stimulation within a single menstrual cycle (dual stimulation) [87,88]. Clomiphene citrate (CC) administration during the luteal phase has the advantage that it allows sufficient time up to implantation in order to overcome the adverse CC effect on the implantation potential of the endometrium and on the early pregnancy.…”
Section: Luteal Phase Ovulation Inductionmentioning
confidence: 99%
“…Clomiphene citrate (CC) administration during the luteal phase has the advantage that it allows sufficient time up to implantation in order to overcome the adverse CC effect on the implantation potential of the endometrium and on the early pregnancy. A 2015 meta-analysis comparing CC use during the late luteal phase versus the early follicular phase concluded that luteal induction yielded more oocytes and improved endometrial thickness without this translating into higher pregnancy rates or reduced miscarriage rates [88]. Although the protocols vary between the studies on luteal ovulation induction (in terms of type and timing of stimulation-early/mid/late luteal phase), it would be interesting to see if this approach affects PL rates.…”
Section: Luteal Phase Ovulation Inductionmentioning
confidence: 99%
“…Numerous pairwise meta-analyses have tried to identify the efficacies of the above-mentioned therapies in CCR-PCOS patients 5–9 . However, traditional meta-analyses are not based on the full range of all widely used therapies and give limited suggestions to choose the most efficacious therapy for mono-ovulation in CCR-PCOS patients.…”
Section: Introductionmentioning
confidence: 99%